Anti-oxidized macrophage migration inhibitory factor (oxMIF) antibody imalumab (BAX69) in advanced solid tumors: Final results of first-in-human phase 1 study - Mahalingam, Devalingam; Halama, Niels; Jäger, Dirk (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: MIF is a pleiotropic cytokine involved in tumor cell proliferation, angiogenesis, and inflammation. oxMIF is the pathogenic isoform found in tumor and its stroma. Imalumab is a novel recombinant, fully human, monoclonal antibody that targets oxMIF, with antitumor activity.Methods: Dose escalation study (3 + 3 design). Primary endpoint was maximum tolerated dose (MTD). Secondary endpoints were antitumor activity, safety, pharmacokinetics (PK), and pharmacodynamics (PD). Patients (pts), previously treated with other agents, received intravenous (IV) imalumab [28-d cycles; 2 dose schedules]: biweekly in all solid tumors (Q2W); weekly in metastatic colorectal cancer (mCRC), metastatic ovarian cancer (OvCa), and metastatic non-small cell lung cancer (NSCLC) (QW).Results: 50 pts dosed on the trial: 19 (Q2W) in 6 cohorts (1, 3, 10, 25, 37.5, and...